2008
DOI: 10.1136/bjo.2008.140533
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 23- and 25-gauge transconjunctival sutureless vitrectomies for idiopathic macular holes

Abstract: 23-gauge TSV appears to be as safe and effective as 25-gauge TSV in macular hole surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 19 publications
6
30
0
3
Order By: Relevance
“…The anatomical closure rates compare very favourably with those of other published series looking at PVT and intravitreal gas tamponade with closure rates of 89-100% 5, 12-14 and vitrectomy alone with intravitreal gas tamponade demonstrating a closure rate of 96%. 14,15 The incidence of inducing iatrogenic retinal breaks in 20-gauge vitrectomy for macular hole (without ILM peeling) has been reported as 3.2% with a hole closure 15,18 Macular hole surgery is associated with a higher incidence of causing iatrogenic retinal breaks than vitrectomy surgery for other vitreoretinal pathology, 19,20 presumed to be due to the surgical induction of a posterior vitreous detachment. Induction of the posterior vitreous detachment can cause a tractional retinal break usually near the vitreous base inferiorly.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical closure rates compare very favourably with those of other published series looking at PVT and intravitreal gas tamponade with closure rates of 89-100% 5, 12-14 and vitrectomy alone with intravitreal gas tamponade demonstrating a closure rate of 96%. 14,15 The incidence of inducing iatrogenic retinal breaks in 20-gauge vitrectomy for macular hole (without ILM peeling) has been reported as 3.2% with a hole closure 15,18 Macular hole surgery is associated with a higher incidence of causing iatrogenic retinal breaks than vitrectomy surgery for other vitreoretinal pathology, 19,20 presumed to be due to the surgical induction of a posterior vitreous detachment. Induction of the posterior vitreous detachment can cause a tractional retinal break usually near the vitreous base inferiorly.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was not statistically significant (P=.22). Smaller studies [8][9][10]12 demonstrated a statistically nonsignificant trend for fewer intraoperative retinal tears, and others 16,18,20,21 reported no intraoperative breaks in either group. To the best of our knowledge, our study is the first that has found a statistically significant reduction in the rate of intraoperative retinal break formation using transconjunctival cannulated PPV.…”
Section: Commentmentioning
confidence: 99%
“…‹diyopa-tik makula deli¤i tedavisinde 23-G ve 25-G TSV uygulanan hastalar›n karfl›laflt›r›ld›¤› bir çal›flmada 25-G grubunda makula deli¤i kapanma oran› %92 olarak bildirilmifltir. Ayn› çal›flmada 25-G grubunda görme keskinli¤i 20/80'den 20/34'e yükselmifltir (17). Bizim çal›flmam›zda da benzer flekilde anatomik baflar› %92,3 olarak saptanm›flt›r.…”
Section: Tart›flmaunclassified
“…Makula deli¤i cerrahisinde anatomik baflar› oran› 20-G PPV sonras› %87,2-100, 23-G TSV sonras› %80-96 oldu¤u çeflitli yay›nlarda bildirilmifltir (17)(18)(19)(20). Makula deli¤i cerrahisinde 20-G ve 23-G PPV ile bildirilmifl olan bu anatomik baflar› oranlar› çal›flmam›zla ve di¤er 25-G TSV çal›flmala-r›yla benzerlik göstermektedir (15)(16)(17).…”
Section: Tart›flmaunclassified
See 1 more Smart Citation